CRIMINAL LAW'S APPROACH TO THE END OF AN ANIMAL'S LIFE - BESSE, Thomas (MEDECINE LEGALE DROIT MEDICAL, 2025)
Criminal law, as a legal discipline that governs only human activities, cannot apprehend the end of an animal’s life in the same way as it apprehends the end of human life. However, the “end of animal life” is likely to receive multiple responses in criminal law. These aim, alternatively, to provide for the repression of acts by which humans provoke an end-of-life situation for animals; or, conversely, to legitimize end-of-life situations for animals provoked by humans.